2017
DOI: 10.1016/j.jes.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid 2-arachidonoylglycerol protects inflammatory insults from sulfur dioxide inhalation via cannabinoid receptors in the brain

Abstract: Sulfur dioxide (SO) pollution in the atmospheric environment causes brain inflammatory insult and inflammatory-related microvasculature dysfunction. However, there are currently no effective medications targeting the harmful outcomes from chemical inhalation. Endocannabinoids (eCBs) are involved in neuronal protection against inflammation-induced neuronal injury. The 2-arachidonoylglycerol (2-AG), the most abundant eCBs and a full agonist for cannabinoid receptors (CB1 and CB2), is also capable of suppressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Several studies have highlighted the regulatory effects of the ECS on neuroinflammatory conditions by modulating the production of cytokines. For instance, 2-AG was shown to prevent the overexpression of TNF-α, IL-1β, and iNOS in a murine model of SO 2 -induced brain inflammation [ 172 ]. MAGL-deficiency leading to increased 2-AG levels also reduced brain PGE 2 and pro-inflammatory cytokine levels following peripheral LPS administration in mice [ 173 ].…”
Section: Neuroinflammation-induced Synaptopathy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Several studies have highlighted the regulatory effects of the ECS on neuroinflammatory conditions by modulating the production of cytokines. For instance, 2-AG was shown to prevent the overexpression of TNF-α, IL-1β, and iNOS in a murine model of SO 2 -induced brain inflammation [ 172 ]. MAGL-deficiency leading to increased 2-AG levels also reduced brain PGE 2 and pro-inflammatory cytokine levels following peripheral LPS administration in mice [ 173 ].…”
Section: Neuroinflammation-induced Synaptopathy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, 2-AG play an important role in inflammation. 2-AG attenuates the stimulation of the organism by proinflammatory factors, such as TNF-α ( Chanda et al, 2017 ) and IL-1β ( Li, et al, 2017 ). Our study found that APEC infection decreased the secretion of 2-AG in the lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…eCB is present and is active in the human body, even if one has not ingested cannabis. Endogenous 2-arachidonylglycerol (2-AG), one of the main eCBs, contributes to the restoration of inflammation-related microvasculature dysfunction caused by overoxidation [ 33 ]. Endogenous 2-AG abolished VCAM-1 and ICAM-1 elevation induced by CB1/2 receptor activation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous 2-arachidonylglycerol (2-AG), one of the main eCBs, contributes to the restoration of inflammation-related microvasculature dysfunction caused by overoxidation [ 33 ]. Endogenous 2-AG abolished VCAM-1 and ICAM-1 elevation induced by CB1/2 receptor activation [ 33 ]. The pleiotropic effects of endogenous 2-AG may prevent and treat depression by abolishing inflammation and vasculature dysfunction.…”
Section: Discussionmentioning
confidence: 99%